Personal Hygiene dan Sanitasi Lingkungan pada Penderita Scabies - Padilah, Sri; Karbito, Karbito; Santoso, Imam (Universitas Malahayati Bandar Lampung, 2025)
Background : Scabies is a contagious skin disease caused by infestation of the mite Sarcoptes scabiei var. hominis. Overcrowded living conditions and poor personal hygiene are the main risk factors contributing to its transmission. This study was conducted to assess the condition of personal hygiene and environmental sanitation at Madarijul Ulum Islamic Boarding School, located in Teluk Betung Barat District, Bandar Lampung City, and to describe their contribution to the potential spread of scabies in the area.Metode : This research employed a descriptive method with a quantitative approach. The sample consisted of 255 students selected using a total sampling technique. Data were collected through direct observation and questionnaire completion using a validated checklist. The data were analyzed descriptively in the form of percentages.Results : The study results showed that the aspects of personal hygiene with the lowest compliance rates were clothing cleanliness (53.73% non-compliant), followed by skin hygiene (52.94%) and towel cleanliness (55.69%). On the other hand, hand and nail hygiene showed a high compliance rate of 94.37%. In terms of environmental sanitation, clean water usage met the required standards (100%), but housing density did not meet the standard at all (100% non-compliant), and temperature and humidity conditions only met the standard in 4.76% of the rooms.Conclusion : It is concluded that the substandard personal hygiene and environmental sanitation conditions in the boarding school significantly contribute to the increased risk of scabies transmission. Infrastructure improvements and continuous education for students are necessary to mitigate the spread of this disease.Keywords: Personal Hygiene, Environmental Sanitation, Scabies, Islamic Boarding SchoolABSTRAKLatar Belakang : Scabies merupakan penyakit kulit menular yang disebabkan oleh infestasi tungau Sarcoptes scabiei var. hominis. Lingkungan hunian yang padat serta kebersihan pribadi yang buruk menjadi faktor risiko utama penyebarannya. Penelitian ini dilakukan untuk mengetahui kondisi personal hygiene dan sanitasi lingkungan di Pondok Pesantren Madarijul Ulum, Kecamatan Teluk Betung Barat, Kota Bandar Lampung, serta menggambarkan kontribusinya terhadap potensi penyebaran scabies di lingkungan tersebut.Metode : Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Sampel dalam penelitian ini berjumlah 255 santri yang dipilih menggunakan teknik total sampling. Data diperoleh melalui observasi langsung dan pengisian kuesioner dengan lembar checklist yang telah divalidasi. Analisis data dilakukan secara deskriptif dalam bentuk persentase.Hasil : Hasil penelitian menunjukkan bahwa aspek personal hygiene dengan tingkat kepatuhan paling rendah adalah kebersihan pakaian (53,73% tidak memenuhi syarat), diikuti kebersihan kulit (52,94%) dan kebersihan handuk (55,69%). Sementara itu, kebersihan tangan dan kuku menunjukkan tingkat kepatuhan tinggi sebesar 94,37%. Dari aspek sanitasi lingkungan, penggunaan air bersih memenuhi syarat 100%, namun kepadatan hunian tidak memenuhi syarat secara keseluruhan (100%) dan suhu serta kelembaban ruangan hanya memenuhi syarat sebesar 4,76%.Kesimpulan : Disimpulkan bahwa kondisi personal hygiene dan sanitasi lingkungan yang belum memenuhi syarat di pondok pesantren berperan signifikan dalam meningkatkan risiko penyebaran scabies. Diperlukan upaya perbaikan infrastruktur dan edukasi berkelanjutan kepada santri.Kata kunci : Personal Hygiene, Sanitasi Lingkungan, Scabies, Pondok Pesantren